The optimal training load for the development of dynamic athletic performance - Wilson, G. J.; Newton, R. U.; Murphy, A. J.; Humphries, B. J. (Medicine & Science in Sports & Exercise, 1993)
Wilson et al (1) examined three different resistance training programs and their effects on performance of dynamic athletic activities. 64 subjects were randomly assigned to one of the training programs or to a control group that performed no training. The three training programs were a traditional weight training program (heavy squats), a plyometric training program (depth jumps), and explosive weight training with a load that maximized mechanical power output (weighted squat jumps). The study lasted 10 weeks. Prior to, after 5 weeks, and after completion of the training program, subjects were tested for performance in a 30-m sprint, a vertical jump with and without a countermovement, a maximal cycle test, an isokinetic leg extension test, and a maximal isometric test. FINDINGS: The weighted squat jump group achieved the best overall results, achieving significant improvements on most of the tests. IMPLICATIONS: Training with a load that maximizes mechanical power output may be the most beneficial for enhancing performance in power activities.